Secretion of Phospholipase DΔ Functions as a Regulatory Mechanism in Plant Innate Immunity. Issue 12 (9th October 2019) - Xing, Jingjing; Li, Xiaojuan; Wang, Xiaohua; Lv, Xueqin; Wang, Li; Zhang, Liang; Zhu, Yingfang; Shen, Qianhua; Baluška, František; Šamaj, Jozef; Lin, Jinxing
Abstract : Membrane microdomains and PLDΔ exocytosis regulate PLDΔ accumulation during penetration resistance in plant innate immunity. Abstract: Plant phospholipase Ds (PLDs), essential regulators of phospholipid signaling, function in multiple signal transduction cascades; however, the mechanisms regulating PLDs in response to pathogens remain unclear. Here, we found that Arabidopsis ( Arabidopsis thaliana ) PLDΔ accumulated in cells at the entry sites of the barley powdery mildew fungus, Blumeria graminis f. sp hordei . Using fluorescence recovery after photobleaching and single-molecule analysis, we observed higher PLDΔ density in the plasma membrane after chitin treatment; PLDΔ also underwent rapid exocytosis. Fluorescence resonance energy transfer with fluorescence lifetime imaging microscopy showed that the interaction between PLDΔ and the microdomain marker AtREMORIN1.3 (AtREM1.3) increased in response to chitin, indicating that exocytosis facilitates rapid, efficient sorting of PLDΔ into microdomains upon pathogen stimulus. We further unveiled a trade-off between brefeldin A (BFA)–resistant and –sensitive pathways in secretion of PLDΔ under diverse conditions. Upon pathogen attack, PLDΔ secretion involved syntaxin-associated VAMP721/722-mediated exocytosis sensitive to BFA. Analysis of phosphatidic acid (PA), hydrogen peroxide, and jasmonic acid (JA) levels and expression of related genes indicated that the relocalization of PLDΔ is crucial for its activation to produce PA and initiate reactive oxygen species and JA signaling pathways. Together, our findings revealed that the translocation of PLDΔ to papillae is modulated by exocytosis, thus triggering PA-mediated signaling in plant innate immunity.